208k views
5 votes
What is the solution to the equation Negative (5 minus (a + 1)) = 9 minus (5 minus (2a minus 3))? a = –5 a = –3 a = 3 a = 5

2 Answers

4 votes

Answer:

-5

Explanation:

User Desmond
by
5.5k points
3 votes

Answer:

a = -5

Explanation:

negative (5 minus (a + 1)) = 9 minus (5 minus (2a minus 3)) can be expressed mathematically as follows.

- (5 - (a + 1)) = 9 - (5 - (2a - 3))

using the principle of PEMDAS, all the parenthesis values are first solved

- (5 - a - 1) = 9 - (5 - 2a + 3)

-5 + a + 1 = 9 - 5 + 2a - 3

collect like terms

-5 + 1 - 9 + 5 + 3 = 2a - a

-5 = a Therefore,

a = -5

User Saumil Shah
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.